THE IMPACT OF GOOD CORPORATE GOVERNANCE IMPLEMENTATION ON FINANCIAL PERFORMANCE: (CASE STUDY ON STATE-OWNED ENTERPRISES LISTED ON THE INDONESIA STOCK EXCHANGE 2022 - 2024) - Indraswari, Dewa Ayu Widya; Diatmika, I Putu Gede; Prayudi, Made Aristia (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
The role of Good Corporate Governance (GCG) is increasingly important in improving the financial performance of companies, especially state-owned companies that have great responsibility to the public. The phenomenon of low efficiency and accountability in a number of state-owned companies in Indonesia raises concerns about the quality of governance and its impact on financial performance. This study aims to determine the effect of GCG implementation on the financial performance of state-owned companies listed on the Indonesia Stock Exchange (IDX) in the 2022–2024 period. The population in this study were all state-owned companies listed on the IDX. The sample was determined using a purposive sampling technique with the following criteria: (1) state-owned companies that are consistently listed on the IDX during the observation period, (2) publish complete annual reports, and (3) have GCG measurement data and financial performance indicators that are publicly accessible. The number of samples obtained was 18 companies. The type of data used is secondary data collected from the official IDX website, company annual reports, and GCG assessment reports published by the Ministry of State-Owned Enterprises. The data analysis technique used is simple linear regression analysis with the help of the SPSS program. Before the regression analysis was conducted, a classical assumption test was conducted first, including normality, multicollinearity, and heteroscedasticity tests. The t-test results showed that the GCG variable had a positive and significant effect on financial performance, with a significance value of 0.001. The results of the determination coefficient test showed that GCG was able to explain variations in financial performance by 88.1%. Based on the results of the study, it can be concluded that the better the implementation of GCG, the higher the company's financial performance. Therefore, state-owned companies need to continue to strengthen the implementation of GCG principles in order to improve their competitiveness and financial accountability in the capital market.